Hospital attendance, malaria prevalence and self-medication with an antimalarial drug before and after the start of COVID-19 pandemic in a sentinel site for malaria surveillance in Gabon - Denise Patricia Mawili-Mboumba; Fanny Bertrande Batchy Ognagosso; Noé Patrick M’Bondoukwé; Jacques Mari Ndong Ngomo; Bridy Chesly Moutombi Ditombi; Ahmed Adissa Agbanrin; Tatiana Nymane; Bedrich Pongui Ngondza; Reinne Moutongo Mouandza; Coella Joyce Mihindou; Dimitri Ardin Mabika Moussavou; Ornella Anaïse Mbang Nguema; et al. (Malaria Journal)
Abstract Background The negative impact of COVID-19 pandemic on healthcare service utilization has been reported in several countries. In Gabon, data on the preparedness for future pandemic are lacking. The aim of the present study was to assess the trends of hospital attendance, malaria and self-medication prevalences as well as ITN use before and during Covid-19 first epidemic waves in a paediatric wards of a sentinel site for malaria surveillance, in Libreville, Gabon. Methods This was a retrospective descriptive and hospital-based survey which was conducted at the Regional Hospital of Melen Estuaire (RHME). Census of files of patients below 18 years of age attending for fever management with a result of malaria biological diagnosis from January 2018 to December 2022 was conducted. Comparison of the prevalence of microscopic malaria, ITN use, self-medication and the fever duration prior the screening before and after year 2020 was performed using bivariate and multivariate analysis. Results Overall, 14428 febrile participants were screened for malaria. A 15% increase in the number of febrile patients was observed between 2019 and 2020 while this rate was above 100% in 2021 and 2022. The frequency of self-medication significantly doubled in 2020 and 2021 compared to the pre-COVID-19 period (p < 0.01). Previous self-medication was more common during the COVID-19 period compared to the COVID-19 one (aOR = 2.15 [1.91–2.42]) (p < 0.01). Among the 7259 (51.2%) patients screened after 3 days of fever onset, self-anti-malarial treatment was reported for 17.5% of them in 2019 and for more than 30% of them from 2020: 33.3% in 2020, 35.0% in 2021 and 32.3% in 2022 (p < 0.01). The median of fever duration was significantly higher in the group of participants with a previous self-medication (p < 0.01). Positive blood smears frequency was higher in the COVID-19 period (35.6%; n = 3876/10868) compared to the pre-COVID-19 period (23.6%) (OR = 1.79[1.59–2.02], (p < 0.01). Conclusion Malaria prevalence and care-seeking behaviours for fever management in children significantly changed during the COVID-19 epidemic phase and subsequent years in the main malaria sentinel surveillance site of Gabon.